Improving Health Security and Intelligence Capabilities to Mitigate Biological Threats. Issue 2 (4th May 2021) - Smith, Marcus; Walsh, Patrick
ABSTRACT: The COVID-19 pandemic has fostered a greater appreciation of the significance of health security and intelligence capabilities. This article examines health security and intelligence capabilities in the United States and other countries, with a view to raising awareness of biological threats across the Five Eyes community. New biotechnologies offer vaccines, therapies, and healthcare solutions, but also present biological threats that must be managed. This article begins by discussing the rise of biological threats and the relative lax regulatory environment in the United States and overseas. The second part then examines the growing importance of health security intelligence and the role it can play in response to this potential threat. The third part focuses on intelligence collection, capability, and threat mitigation, and how this could be mobilized to address harmful impacts of biological threats. The final part of the article provides recommendations for building an intelligence capacity within ICs as well as associated regulatory reforms.